The State of the Stock Market before and After the Government Indonesia 2019-2024 - Irawan, Rini Larasati; Nugraha, Nugraha; Sari, Maya (Budapest International Research and Critics University, 2022)
The purpose of this research is to find out about stock returns, stock risk, return expectations and the correlation coefficient on LQ 45 before and during the 2019-2024 government, to find out the differences in risk in LQ 45 stocks before and during the 2019-2024 government. The research method carried out in this study was a different test using the excel tool, and the results showed that stock returns, risk, at the time before the research were higher than during the 2019-2024 government, while research the correlation coefficient the 2019-2021 government has a stronger correlation coefficient, which means that there is a strong relationship between variables.